Impact of liquid biofertilizer from cocoa shells on the growth and chlorophyll content of sweet peppers (Capsicum chinense L.) in San Martín, Peru - Solórzano, Richard; Cruz, Juancarlos; Gaona-Jimenez, Nery; Lozano, Andi; Díaz-Chuquizuta, Henry; Vallejos-Torres, Geomar; Siqueira-Bahia, Rita de Cassia (Frontiers in Agronomy, 2025)
The growth and yield of sweet peppers are constrained by factors such as fertilization practices and edaphoclimatic conditions, which ultimately threaten global food security in the context of an ever-growing population. This study evaluated the effect of a liquid biofertilizer derived from cocoa husks on the growth and chlorophyll content of sweet pepper (Capsicum chinense) cultivated in San Martín, Peru. The experiment was conducted at the experimental station of the National Institute of Agrarian Innovation in Tarapoto, San Martín, Peru (6°35′00″ S, 76°19′46″ W). A completely randomized design was applied, consisting of five treatments (0, 750, 1250, 2250, and 3000 mL) with 20 plants per treatment, totaling 100 experimental units. The biofertilizer was applied eight days after sowing (days). Plant height, stem diameter, and leaf chlorophyll content were measured at 15, 35, and 85 days. After 85 days, the highest plant height was observed with the 3000 mL and 1250 mL treatments, reaching averages of 29.98 and 28.25 cm, respectively. Stem diameter was maximized with 3000 mL (6.25 cm), whereas the highest chlorophyll content was recorded with 1250 mL, averaging 35.37 SPAD units. These results highlight the potential of liquid biofertilizers produced from cocoa shells to enhance nutrient uptake, increase plant biomass, and improve photosynthetic capacity, thereby contributing to sustainable sweet pepper production.